Circulating angiopoietin-1 to angiopoietin-2 ratio is an independent prognostic factor for survival in newly diagnosed patients with multiple myeloma who received therapy with novel antimyeloma agents - Terpos, E.; Anargyrou, K.; Katodritou, E.; Kastritis, E.; Papatheodorou, A.; Christoulas, D.; Pouli, A.; Michalis, E.; Delimpasi, S.; Gkotzamanidou, M.; Nikitas, N.; Koumoustiotis, V.; et al. (International Journal of Cancer, 2012)
The circulating levels of several angiogenic cytokines [angiopoietin-1 (Ang-1), angiopoietin-2 (Ang-2), vascular endothelial growth factor (VEGF), angiogenin and basic fibroblast growth factor (bFGF)] were evaluated in 174 consecutive patients with newly diagnosed, symptomatic, multiple myeloma (MM). Circulating levels of Ang-1/Ang-2 were reduced in myeloma patients compared to controls, whereas VEGF and angiogenin levels were increased. Reduced angiopoietin-1/angiopoietin-2 ratio correlated with advanced disease features including international staging system (ISS)-3 stage, renal impairment and extensive bone disease. Based on immunohistochemical results in 20 patients (10 with the higher and 10 with the lower values of circulating angiopoietin-2) we found that angiopoietin-2 is expressed by myeloma cells and correlates with increased microvessel density in subsets of patients. Furthermore, Ang-1/Ang-2 ratio correlated with survival. Patients with circulating Ang-1/Ang-2 below or equal to the median value (6.03) had a median survival of 26.3 months compared to 53 months of all others (p = 0.002). Interestingly, this was mainly observed in patients who received first-line therapy with novel agent-based regimens (65% of our patients). Furthermore, a subset of ISS-3 patients with serum Ang-1/Ang-2 above the median value had favourable prognosis (median survival: 45 months versus 17 months of all others; p = 0.0001). The multivariate analysis revealed that low Ang-1/Ang-2 ratio could independently predict for inferior survival in our cohort of patients (relative risk (RR) 2.07, 95% CI 1.50-2.42; p < 0.001). These results highlight the role of angiopoietins pathway in the biology of MM and reveal novel targets for the development of antimyeloma agents. Copyright © 2011 UICC.
Keywords: Angiogenesis; angiopoietin-1; angiopoietin-2; multiple myeloma; Survival